(untitled) (Ágora Journal, 2022)
Francisco Gomes de Avelar was bishop of Algarve between 1789 and 1816, the year of his death. Between 1808 and 1816, he temporarily held the position of Governor of Arms of the Algarve. This paper intends to analyse this prelate, both in his episcopal functions and as Governor of Arms. His action is of great interest, mainly because he was an active enlightened reformer, which can be framed within the scope of the Catholic Enlightenment. His reforms continued the project of Restoration of the Kingdom of Algarve, which was undertaken in the 1760s and 1770s. As Governor, Gomes de Avelar played a crucial role in the military reinforcement of the Algarve border, as well as in the instruction for repairing the regional communication routes. We based this study mainly on printed documentary sources authored by Gomes de Avelar, punctually complemented by the reading and interpretation of some relevant manuscript and archival sources.